2019
DOI: 10.1038/s41409-019-0474-8
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review of defibrotide studies in the treatment of veno-occlusive disease/sinusoidal obstruction syndrome (VOD/SOS)

Abstract: Veno-occlusive disease (VOD), also called sinusoidal obstruction syndrome (SOS), is a potentially life-threatening complication of hematopoietic stem cell transplantation (HSCT) conditioning or high-dose nontransplant chemotherapy. VOD/SOS with multi-organ dysfunction (MOD) is associated with a mortality rate of > 80%. Defibrotide (25 mg/kg/day) is approved to treat hepatic VOD/SOS with renal or pulmonary dysfunction post HSCT in the United States and to treat severe hepatic VOD/SOS in patients > 1 month of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 46 publications
(123 reference statements)
1
52
0
1
Order By: Relevance
“…Data from these important studies are quite superimposable and further confirmed by a systematic review of the literature, which found out 100-day survival of 41% in patients with MOD and 71% in those without MOD (97).…”
Section: Treatment and Outcomementioning
confidence: 80%
“…Data from these important studies are quite superimposable and further confirmed by a systematic review of the literature, which found out 100-day survival of 41% in patients with MOD and 71% in those without MOD (97).…”
Section: Treatment and Outcomementioning
confidence: 80%
“…It is worth noting that defibrotide is currently the sole medication approved for VOD/ SOS [33], and there is little evidence of other emerging therapies for VOD/SOS under development. A pooled analysis of clinical trials found that among HSCT recipients treated for VOD/SOS with defibrotide at or close to the approved dose of 25 mg/kg/day, day +100 survival following HSCT was 56% (95% confidence interval [CI], 49% to 63%) overall, including rates of 44% (95% CI, 35% to 52%) in patients with MOD and 71% (95% CI, 67% to 75%) in patients without MOD [34].…”
Section: Importance Of Vod/sos Risk Calculationmentioning
confidence: 99%
“…In a systematic review of defibrotide studies, a random-effects model was used for pooling data [68]. A total of 10 studies with 1,691 patients who received defibrotide at or close to the approved dosage of 25 mg/kg/day were included.…”
Section: Pooled Analysis Of Clinical Trialsmentioning
confidence: 99%
“…For patients with MOD and without MOD, day +100 survival was 44% (95% CI, 35-52%) and 71% (95% CI, 67-75%), respectively. Safety results were not pooled for this review due to differences in how adverse events were reported, but the range of adverse clinical events was consistent with the known safety profile of defibrotide [68]. Similarly, an observational study from the Center for International Blood and Marrow Transplant Research (CIBMTR) reported that patients with severe VOD/SOS who received defibrotide (n = 41) had an improved rate of resolution of VOD/SOS at day +100 (51%) relative to patients not treated with defibrotide (29%; n = 55) [69].…”
Section: Pooled Analysis Of Clinical Trialsmentioning
confidence: 99%